PEMIKIRAN PENDIDIKAN ABDURRAHMAN SALEH ABDULLAH (Resensi Buku â€œTeori-teori Pendidikan Berdasarkan Al-Quranâ€) - Muhammad Tang. S (Fakultas Agama Islam Universitas Kutai Kartanegara, 2018)
The objectives of education, materials and methods of pangajaran in Islam have beenÂ discussed in the Qur'an. The basics regarding practical issues are essential issues in order toÂ achieve the desired goals. This essay is in the form of a review of Abdurrahman SalehÂ Abdullah's work entitled: